Site of semen deposition and fertility in lactating beef cows synchronized with GnRH and PGF2α - G.C. Lamb; K. E. Thompson; K. Anderson; David M. Grieger; Timothy G. Rozell; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1998)
Our objective was to determine the effect of site of semen deposition on pregnancy rate in beef cows inseminated at a fixed time or after observed estrus. Cows were synchronized with a combination of gonadotropin-releasing hormone (GnRH) prostaglandin-F α (PGF). GnRH was injected 7 days before PGF (day 0; first of breeding season). The trial was conducted at two locations, one in Kansas (147 cows) and one in Colorado (313 cows). At each location, cows were assigned to be inseminated after observed estrus (ESTRUS-AI) or at a fixed time (TIMED-AI). Within these two groups, cows either were inseminated in the uterine body (BODY-bred) or in both uterine horns (HORN-bred). Cows in the ESTRUS-AI group were observed for estrus each morning and evening until day 5 afterPGF and then inseminated 12 hr after first detected estrus. Cows in the TIMED-AI group received a second dose of GnRH on day 2 and were inseminated at that time (48 to 56 hr after PGF). Heat response, AI conception rate, and pregnancy rate were analyzed for BODY-bred and HORN-bred cows within each treatment at each location. No differences in these variables occurred between locations, so the results were combined. Within the ESTRUS-AI group, neither conception rate (70% vs. 73%) nor pregnancy rate (39% vs. 40%) was different between BODY-bred and HORN-bred cows respectively. Pregnancy rate within the TIMED-AI group tended (P=.09) to be greater for BODY-bred (53%) compared to HORN-bred (42%) cows. When BODY-bred and HORN-bred treatments were combined, the pregnancy rate of TIMED-AI cows (48%) tended (P=.07) to be greater than that of ESTRUS-AI cows (39%). Timed-insemination resulted in a greater pregnancy rate than inseminating cows according to estrus. No advantage was seen in conception rates when semen was deposited in the uterine horns compared to the uterine body.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; AI; Timed insemination; Horn breeding; Estrous synchronization; Cows